Electronic commerce adoption and implementation in logistic industry: Penang port area perspective - Omar, Mohd. Adan; Hussain, Azham; Saad, Mohd. Nizam (Östereichische Computer Gesellschaft, 2005)
The Internet-Based Electronic commerce (E-Commerce) is rapidly emerging as an entirely new method to conduct business and to interact with customers, suppliers, competitors, and the government. An understanding of the current Electronic Data Interchange (EDI) status is essential for the successful of any E-Commerce initiatives in Malaysia. Thus, this study seeks to provide such an empirical base. The purpose of this study is to measure the use of electronic information exchange in the Malaysian logistic industry as part of the initiatives of E-Commerce. This study will specifically emphasize the Internet-based EDI system usage in shipping industry. The results indicated that the level of awareness among respondent’s companies (which is considered us small and medium companies) to the potential benefits of E-Commerce implementation in logistic industry has increased. Despite the EDI usage at Penang Port were high in terms of volume; however the usage in terms of diversity, breadth and depth were still very low and limited. The extent to which EDI applications are implemented in different business transactions of shipping and forwarding agencies were found to be limited where only a few business partners and certain transactions involved. Investigation on the feasibility factors reveals that the availability of EDI applications, management support, and initial investment are the three most influenced factors cited by the responding companies.